2021
DOI: 10.1186/s12933-021-01413-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of glycated hemoglobin A1c levels with cardiovascular outcomes in the general population: results from the BiomarCaRE (Biomarker for Cardiovascular Risk Assessment in Europe) consortium

Abstract: Background Biomarkers may contribute to improved cardiovascular risk estimation. Glycated hemoglobin A1c (HbA1c) is used to monitor the quality of diabetes treatment. Its strength of association with cardiovascular outcomes in the general population remains uncertain. This study aims to assess the association of HbA1c with cardiovascular outcomes in the general population. Methods Data from six prospective population-based cohort studies across Eur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 48 publications
(63 reference statements)
0
29
2
1
Order By: Relevance
“…A wealth of evidence documents the association of greater HbA1c levels with adverse cardiovascular outcome in various cohorts [7] . In the setting of intensified diabetes mellitus therapies, poor glycemic control as reflected by high HbA1c levels was associated with increased all-cause mortality [3] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wealth of evidence documents the association of greater HbA1c levels with adverse cardiovascular outcome in various cohorts [7] . In the setting of intensified diabetes mellitus therapies, poor glycemic control as reflected by high HbA1c levels was associated with increased all-cause mortality [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Hemoglobin A1c (HbA1c) reflects long-term glycemic control and is central to the diagnosis and management of diabetes mellitus [ 1 , 2 ]. Elevated HbA1c is associated with an increased risk of cardiovascular events among diabetic and non-diabetic patients [2] , [3] , [4] , [5] , [6] , [7] ; with diabetic atherosclerosis manifesting within the arterial wall with accelerated disease progression and impaired arterial wall remodeling [8] . However, elevated HbA1c-levels are frequently concomitant with multiple other atherogenic risk factors, including dyslipidemia, hypertension, smoking and obesity which are all known drivers of plaque progression [9] , [10] , [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the role of HbA1c outside of diabetes has received increasing attention. It has been shown that the HbA1c level is significantly associated with the risk of cardiovascular disease even in non-diabetic populations [ 7 , 8 ]. In addition, HbA1c is a reliable risk factor for all-cause and cardiovascular mortality in both diabetic and non-diabetic populations [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the HbA1c level is significantly associated with the risk of cardiovascular disease even in non-diabetic populations [ 7 , 8 ]. In addition, HbA1c is a reliable risk factor for all-cause and cardiovascular mortality in both diabetic and non-diabetic populations [ 8 , 9 ]. Recent studies have attempted to extend the role of HbA1c by including it as a useful component of the definition of metabolic syndrome [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…HbA1c compared to OGTT has low sensitivity for the diagnosis of prediabetes and T2D in PCOS [ 71 ], but HbA1c is a better predictor of cardiovascular disease and overall mortality than blood glucose during OGTT [ 71 , 72 ]. HbA1c could be used as an indicator for both increased metabolic and vascular risk [ 72 , 73 ], and prospective measurement of HbA1c is more feasible than measurement of fasting glucose or OGTT in a clinical setting. In some countries, the use of OGTT is preferable to HbA1c and fasting glucose, as other methods are unavailable or unreliable [ 70 ].…”
Section: Discussionmentioning
confidence: 99%